Single-Arm, Multicenter Phase I/II Clinical Trial for the Treatment of Envenomings by Massive Africanized Honey Bee Stings Using the Unique Apilic Antivenom - Barbosa, Alexandre Naime; Ferreira, Rui Seabra; de Carvalho, Francilene Capel Tavares; Schuelter-Trevisol, Fabiana; Mendes, Mônica Bannwart; Mendonça, Bruna Cavecci; Batista, José Nixon; Trevisol, Daisson José; Boyer, Leslie; Chippaux, Jean-Philippe; Medolago, Natália Bronzatto; Cassaro, Claudia Vilalva; et al. (Frontiers in Immunology, 2021)
We evaluated safety, optimal minimum dose, and, preliminary effectiveness of a new generation Africanized honey bees Antivenom. A phase I/II, multicenter, non-randomized, single arm clinical trial involving 20 participants showing multiple stings. Participants have received either 2 to 10 vials of AAV based on the number of stings or a predefined adjuvant, symptomatic and complementary treatment schedule. Primary safety endpoint was the presence of early adverse reactions within the first 24 h after treatment. Preliminary efficacy through clinical evolution, including laboratory tests, was assessed at baseline and at various times over the following four weeks. ELISA assays and mass spectrometry estimated the venom pharmacokinetics before, during and after treatment. Twenty adult participants, 13 (65%) males and 7 (35%) females, with a median age of 44 years and mean body surface of 1.92 m2 (median = 1.93 m2) were recruited. Median number of stings was 52.5 ranging from 7 to more than 2,000. Envenoming severity was classified as 80% mild, 15% moderate, and 5% severe. According to the protocol, 16 (80%) participants received two AAV vials, 3 (15%) six vials, and one (5%) 10 vials. There was no discontinuation of the protocol due to adverse events and there were no serious adverse events. One patient showed moderate adverse events with only transient itchy skin and erythroderma. All participants completed the intravenous infusion of antivenom within two hours and there was no loss of follow-up after discharge. ELISA assays showed venom concentrations varying between 0.25 ng/mL and 1.479 ng/mL prior to treatment. Venom levels decreased in all cases during the hospitalization period. Surprisingly, in nine cases (45%), despite clinical recovery and without symptoms, the venom levels increased again during outpatient care 10 days after discharge. Mass spectrometry showed melittin in eight participants 30 days after the treatment. Considering the promising safety results of the investigational product for the treatment of massive Africanized honeybee (Apis mellifera) attack, added to efficacy reflected in clinical improvement and immediate suitable decrease in blood venom level, the AAV has shown to be safe for human use.